Serum HBV pregenomic RNA exhibited opposite associations with NKdim and NKbright cell immunity in treatment-naïve chronic hepatitis B patients. Issue 7 (30th July 2021) - Gu, Yurong; Huang, Zexuan; Li, Xiaoyan; Chen, Youming; Liao, Chunhong; Bi, Yanhua; Huang, Yuehua
Abstract: Hepatitis B virus (HBV) pregenomic RNA (pgRNA) is a new biomarker that reflects HBV replication, but its relationship with natural killer (NK) cell immunity in chronic hepatitis B (CHB) is unknown. We assessed serum HBV pgRNA levels in 323 CHB patients by reverse transcription-polymerase chain reaction, assessed cytokine production and activation and inhibitory markers of NK cells by flow cytometry, and measured serum cytokines by enzyme-linked immunosorbent assays (ELISAs). Among the different CHB phases, the serum HBV pgRNA level was highest in the immune-tolerant (IT) and immune-active (IA) phases. Regarding NK and NK dim cells, HBV pgRNA was negatively associated with frequencies, but positively associated with NKp44 and NKp46 expression (activation markers). Regarding NK bright cells, serum HBV pgRNA was positively associated with frequency and programmed cell death protein 1 (PD1) expression (inhibitory marker), but negatively associated with NKp44 and NKp46. Serum HBV pgRNA was not associated with NKp30 (activation marker) on NK cells or subsets. Lastly, serum HBV pgRNA was positively correlated with the levels of serum IL-7 and IL-12P40 (NK cell-promoting cytokines) and negatively correlated with serum prostaglandin E2 (PGE2) level (which negatively regulates NK cells). In conclusion, we found varied relationships between serum HBV pgRNA and NK cells and subsets, indicating that HBV pgRNA may play a complicated role in NK cell-related immunity, providing new information on HBV and host immunity.